The unfairest of them all - Hale, Shannon (New York ; Boston : Little, Brown Books and Company, 2014)
In the aftermath of Legacy Day, Raven Queen, reluctant leader of the Rebels, and Apple White, head of the Royals, work together when an Ever After High student, Maddie, gets in trouble, threatening all of their Happily Ever Afters.
Keywords: Fairy tales -- Fiction; Characters in literature -- Fiction; Fate and fatalism -- Fiction; Friendship -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; JUVENILE FICTION / Toys, Dolls, Puppets; JUVENILE FICTION / Fairy Tales & Folklore / General